Assessment and monitoring of the health status of the Talassemtane fir forest (Western Rif, Morocco) - Lamrhari, Hajar; Ben Said, Mariem; Aadel, Taoufik; Bouziane, Hassan (Ecological Questions, 2026)
The endemic Talassemtane fir forest (northern Morocco) represents an ecosystem of great ecological and socioeconomic values, but has not been subject of any phytosanitary monitoring. This monitoring is crucial for providing information on forest health and supporting conservation actions. We sampled 200 trees from ten plots at the Talassemtane fir forest, measured their dendrometric features, and assessed forest dysfunction (branch mortality, leaf deficit, pruning, and biotic and abiotic damages) and stability indicators (Relative Crown Length and Index of Biodiversity Potential) from 2015 to 2018. The distribution of the sampled trees according to the circumference and total height classes revealed continuous stand regeneration. We found a gradual improvement in the crown status for almost all sampled trees. The pruning was low in 2015 and absent between 2016 and 2018. The most common damages were the abnormal colouring and consumption of leaves, especially by pine processionary moth and looper outbreaks. Lichens colonized about 40% of the sampled trees, reflecting environmental and microclimatic conditions, while biotic damages did not exceed 1.5% of the trees. The majority of plots present a high number of trees with a Relative Crown Length greater than half of the total height. The sampled trees showed significant vigour and high vitality, which would express a stable environmental equilibrium. The Index of Biodiversity Potential revealed a good forest capacity to host biodiversity and significant stability. Our pioneer permanent plot network should be continuously monitored to help the long-term management and conservation of this endemic ecosystem.